Digital Marketing Exploitation Training in an Effort to Increase the Potential Selling Power of Female UMKM in Pekanbaru City - Putri, Librina Tria; Rahmawati, Rahmawati; Salis, Muhammad; Ikhsan, Afdhol (PT FORMOSA CENDEKIA GLOBAL, 2023)
Digital marketing training is the key to developing UMKM, especially women, in Pekanbaru City. Even though UMKM have a vital role in the local economy, many of them still experience difficulties in adopting online marketing. In the digital era, an online presence is not just a necessity, but a great opportunity to expand markets and increase product selling power. In addition, the impact of the COVID-19 pandemic strengthens the need for adaptation to consumer behavior that shifts to online platforms. Digital marketing strategy training is a crucial solution to help women UMKM survive and grow amidst these challenges, increase their competitiveness and expand their market reach. Community service activities are expected to provide the knowledge, skills and tools needed so that women UMKM can successfully exploit the potential of digital marketing.